A profile of little athletes' injuries and the prevention methods used - Coulon, L.; Lackey, G.; Mok, M.; Nile, D. (Journal of Science and Medicine in Sport, 2001)
This study provides a profile of injuries sustained by Little Athletes and the injury prevention strategies they employed. The sample comprised 388 registered Little Athletes from seven Sydney New South Wales Clubs. Results from the survey and fieldwork suggested that at least one out of five Little Athletes had one or more injuries resulting from their participation in the current season. However, athletes aged under 11 to under 15 years were more likely to be injured than those in the younger age groups. The older athletes were also likely to have sustained more than four injuries during the season. Athletes reported low use of both warm up and warm down methods. Coaches, age managers and parents were portrayed as the key providers of information concerning injury prevention strategies. It was therefore noted that a valuable opportunity exists to create and design an innovative, age progressive educational package for Little Athletes, parents and coaches.